PENGARUH JENIS PEKERJAAN DENGAN KETIDAK AKTIFAN IBU BERKUNJUNG KE POSYANDU DESA JALEN KECAMATAN BALONG KABUPATEN PONOROGO - Ambika Kurnia Mustikawati (AKADEMI KEBIDANAN HARAPAN MULYA PONOROGO, 2019)
Based on the Register Cohort weighing a toddler on November 10, 2018 atPosyandu Jalen there are 65 men mother toddler retrieved 25 (38.4%) bringing his son tothe always active and 40 posyandu (61.6%) mother toddler people not actively bring hisson to the Posyandu. A preliminary study of 10 people who are not active toddler'smother obtained work mother who brings her son off to their busy work posyandu 3(30%) as civil servants, 3 (30%) as farmers and 4 (40%) as a trader.Type of this research is quantitative approach to koresional and use the form ofcross sectional. The sample was all mother toddler who came to the village of posyanduJalen Subdistrict Balong Ponorogo in January 2019 with the inclusion criteria and aretaken using the technique of accidental sampling. The instruments used in this study usingquestionnaire. Analysis of the influence between the variable using the correlation testchi square with 0.05 significant level.The work of mothers in the village of Posyandu Jalen Subdistrict BalongPonorogo almost half of the respondents i.e. as many as 25 (38.4%) working as the IRTand as many as 20 (30.9%) working as a trader. The aktifan visit the mother of most ofthe respondents (58.5%) i.e., 38. There is the influence of the type of work with theinactivity of the mother paid a visit to the village of posyandu Jalen Subdistrict BalongPonorogo with statistical test p = 0.000. The kind of work that is most influentialWorking Moms as traders who are all as many as 20 respondents (100%) and motherworking as CIVIL SERVANTS who are all as many as 7 respondents (100%) not active inthe visit of the posyandu.Solutions carried out visits to posyandu on the schedule set by the posyandu andliveliness for a visit should arise on the mother because the toddler is a define in time isgrowing important role, will happen a whole person, due to his physical growth aspectshave first gained attention as well as conduct posyandu cadre in order to approach withentwined good cooperation.